BIOMEDICAL PERFORMANCE IN HEMATOLOGY (CIPEEX, 2025)
Introduction: Hematology is a fundamental area of Biomedicine that studies blood, its components and related diseases. The performance of the biomedical in hematology is essential for the diagnosis, monitoring, and treatment of various hematological pathologies, such as anemia, leukemia, and coagulation disorders. The biomedical performs laboratory analyses that provide crucial data for clinical decision-making, contributing directly to the patient's health. The importance of this action has been widely recognized, highlighting the need for in-depth technical and scientific knowledge. Objective: To conduct a bibliographic study on the performance of biomedical professionals in hematology, highlighting their responsibilities, competencies and the relevance of this profession in the context of public and private health. Methodology: A narrative literature search was carried out between March and May 2025, using the SciELO, Science Direct, and NHS Healthcare Careers databases. The keywords used were: "biomedical", "hematology", "laboratory analysis", "hematological diagnosis" and "health science". Complete scientific articles, reviews and institutional documents published in Portuguese and English that addressed the professional performance of biomedical professionals in hematology were selected. Results: The research showed that the biomedical in hematology plays a crucial role in performing laboratory tests that evaluate blood parameters, such as blood count, coagulogram, hemoglobin dosage and identification of abnormal cells. The biomedical doctor is responsible for the analysis and interpretation of the results, ensuring the quality and reliability of laboratory data, which are essential for the accurate diagnosis and therapeutic follow-up of patients. In addition, the biomedical professional works in the implementation of quality control protocols and in the validation of new diagnostic methods, contributing to the innovation and safety of laboratory procedures. Their work involves collaboration in multiprofessional teams, participating in clinical discussions and assisting in the definition of therapeutic strategies. The biomedical in hematology must possess advanced technical skills, knowledge in molecular biology and immunology, as well as be up to date with emerging laboratory technologies. Continuous training is essential to keep up with innovations in the area and ensure excellence in patient care. A recent study highlights the importance of the role of biomedical professionals in transfusion hematology, emphasizing their role in ensuring transfusion safety and in the management of blood banks. The professional must master technical and ethical skills for effective performance in this sub-area, reinforcing the need for constant updating and specialization. Conclusion: The biomedical doctor in hematology is an indispensable professional for the diagnosis and treatment of blood diseases, acting with technical and scientific responsibility. Their contribution is vital to the quality of laboratory services and to positive clinical outcomes. The appreciation and recognition of this performance are fundamental for the advancement of Biomedicine and for the improvement of public health.